A facile access for multisubstituted trifluoromethyl olefins by visible light catalysis. (2nd March 2021) - Ren, Shujian; Fu, Jiahui; Cheng, Dongping; Li, Xiaonian; Xu, Xiaoliang
Graphical abstract: Highlights: Facile synthesis of multisubstituted trifluoromethyl olefins by visible light photoredox. Broad scope of alkylboronic acids and Boc-modified trifluoromethylated Baylis-Hillman adduct. Moderate to good yields, simple operation and mild conditions. Abstract: Induced by visible light, a green approach for the highly substituted trifluoromethyl olefins has been developed by using alkyl boronic acid as a carbon radical precursor and the Boc-modified trifluoromethylated Baylis-Hillman adduct (BMTBHA) as an acceptor. This method starts from 1, 1-disubstituted olefins without the external stoichiometric oxidant.